Coronavirus Disease 2019 Regulatory Response in United States-Assisted Living Communities: Lessons Learned - Dys, Sarah; Winfree, Jaclyn; Carder, Paula; Zimmerman, Sheryl; Thomas, Kali S. (Frontiers in Public Health, 2021)
COVID-19 has disproportionately affected residents, their families, staff, and operators of congregate care settings. Assisted living (AL) is a type of long-term care setting for older adults who need supportive care but not ongoing nursing care, and emphasizes a social model of care provision. Because AL is a type of long-term care, it has at times been referenced along with nursing homes in discussions related to COVID-19, but not recognized for its different care practices that pose unique challenges related to COVID-19; in that manner, it has largely been left out of the COVID-19 discourse, despite the fact that more than 811,00 older adults live in AL. To identify COVID-19 issues specific to AL, stakeholders with expertise in AL operations, policy, practice, and research (n=42) were recruited to participate in remote interviews between July and September 2020. Using thematic analysis, we derived the following overarching themes: 1) Policy makers are disconnected from and lack an understanding of the AL context; 2) AL administrators were left to coordinate, communicate, and implement constantly changing guidelines with little support; 3) AL organizations faced limited knowledge of and disparate access to funding and resources; 4) State-level regulatory requirements conflicted with COVID-19 guidelines resulting in uncertainty about which rules to follow; and 5) AL operators struggled to balance public health priorities with promoting their residents’ quality of life and wellbeing. To develop evidence-informed policy and avoid unintended consequences, AL operators, direct care workers, residents, and clinicians practicing in these settings should have opportunities to provide feedback through the policy development process, both state and national.